The interplay between ethics, justice, corporate social responsibility, and performance management sustainability - Tziner, Aharon; Persoff, Menachem (Frontiers in Psychology, 2024)
In the increasingly volatile 21st century globalized and interconnected business landscape, organizations face increasing scrutiny concerning their ethical behavior, social responsibilities, and overall performance. This paper looks at some of the factors that link the notions of ethics, justice, and Corporate Social Responsibility (CSR), with an eye to their theoretical underpinnings and complexities and their relationship to the efficient and sustainable operation of Sustainable Performance Management (with special emphasis on CSR). Drawing on theoretical foundations and empirical evidence, we provide practical recommendations for organizations to promote ethics, justice, CSR, and effective and sustainable performance management. Suggestions include fostering ethical leadership by modeling ethical behavior and promoting ethical decision-making. We believe that the suggested practical measures may bridge the gap between academic perspectives and the practical realities of ensuring favorable, sustainable, work climates and work processes.